UNKNOWN FLASHBACKS ABOUT IVAN FRANKO: NEW STROKES TO RELATIONSHIPS OF POET WITH GALICHRUSS ELITE - Піхманець, Р. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is devote to almost unknown bibliographer Vasyl Franko and his flashbacks about the famous relative. They complement and underline the difficult and heterogeneous picture of relations of Ivan Franko with Galich-Russ elite which helps to understand some «dark places» in his biography.